Quality Of Mochi With Red Dragon Fruit Peel Juice Substitution - Khairiyah, Zahratul; Andriani, Cici; Elida, Elida; Yasih, Fitri (Universitas Negeri Padang, 2025)
Mochi is a Japanese specialty made from glutinous rice flour that is easily modified into attractive food with various colors. Mochi is a popular food among the public, but many use synthetic dyes. Dragon fruit peel can be used as a natural coloring ingredient in mochi by substituting red dragon fruit peel juice to increase its functional value. This study aims to analyze the effect of 30%, 50% and 70% red dragon fruit peel juice substitution on the quality of color, aroma, texture and taste of mochi. This type of research is a pure experiment with the Complete Randomized Design (CRD) method, with three repetitions. Data were analyzed using Analysis of Variance (ANOVA), if Fcount> Ftable then continued the Duncan test. The results of this study indicate that there is a significant effect on the substitution of dragon fruit peel juice as much as 30%, 50% and 70% on the quality of color (pink rose) and aroma quality (not smelling typical of red dragon fruit peel). While the quality of taste and texture did not show a significant effect. The best results of color quality are found in X2 (3.67) with pink rose color category, aroma quality is found in X0 (5.00) with the category of not smelling typical dragon fruit skin, moist texture quality is found in X2 and X3 (3.89) with moist category, chewy texture quality is found in X0 (4.11) with chewy category, soft texture quality is found in X2 and X3 (3.89) with soft category and in taste quality is found in X0 (5.00) with the category of not tasting typical dragon fruit skin. The results showed that there was a significant effect of red dragon fruit peel juice on color quality (pink rose) and taste quality (no taste of dragon fruit peel).